Bad Bastards?: Tattooing, Health, and Regulation in Twentieth-Century Vancouver - Jelinski, Jamie (Urban History Review / Revue d'histoire urbaine, 2018)
Using local newspapers and archival documents from the City of Vancouver Archives, this article investigates how state actors—namely the city of Vancouver’s Health Department—attempted to regulate professional tattooing in Vancouver. Simultaneously, I consider how tattooists understood health and sanitation relative to tattooing and, in the process, responded to and challenged regulation. In doing so, I investigate the complex relationship between Vancouver’s professional tattooists and state actors, focusing on the methods used to regulate tattooing. I argue that although unfounded or inadequately established health concerns typically concealed efforts to control tattooing, tattooists worked within and against regulation to maintain a presence in Vancouver.